Financial Health: Examining the Ability of Malaysian Household in Servicing Their Debts - Abdul Rahman, Nora Azureen; Kosim, Zunarni; Siew, Goh Yeok (Serials Publications, 2017)
This study is motivated by the persistent increased in household debts among Malaysian. The increasing trend of household debts raised concerns about the ability of the households to service their debts; especially when bankruptcies rates among Malaysian increase rapidly. Hence, this study seeks to examine the ability of the households in servicing their debts by looking at the association between loan features and types of household loans, and the post-loan debt service ratio. Using estimated logit model, the results show that household loans are associated with different loan features, which also indicates the ability condition of the household to service their debts. The post-loan debt service ratio shows that borrowers of certain types of loans have difficulties or less ability to service their debts. Further, the socio-demographic factors present the association of the borrowers’ characteristics with types of household loans. The results show that the ability to repay debts is different between gender, races, education and employment. The study is conducted on households in three northern states of Malaysia